Allograft and Patient Outcomes of a Tumourectomized Kidney Transplant Program: The Western Australia Experience. (July 2018) - He, Bulang; Mou, Lingjun; Delriviere, Luc; Jaques, Bryon; Lim, Wai
Abstract : Background: There is an increased utilization of marginal donor kidneys for transplantation due to the shortage of donor kidneys. Patients with a small renal cell cancer occasionally undergo radical nephrectomy, which represents an opportunity to consider the utilization of these kidneys for transplantation that would otherwise be discarded. We report the long-term outcome of kidney transplant recipients who have received kidneys from live-unrelated donors with resected small renal cell cancers of less than 3 cm. Materials & Methods: The potential recipients were informed and consent was obtained before they were listed for kidney transplantation by using a kidney graft, in which a small tumor was excised. The referral was sent from urologists to transplant team when a radical nephrectomy was decided as an option for treating a renal tumor. As such, the patient was offered an option of kidney donation after radical nephrectomy and the informed consent was signed. In our structured program, the decision for partial or radical nephrectomy for management of a small renal mass was purely made between the discussion of a patient and his or her treating urologist. The selection criteria for the potential donor and recipient have been established prior to implementation. The frozen section was performed after tumor excision on bench table to ensure the margin was clear prior to transplantation. The recipients were selected as age over 60 years or age 55 with urgent need for transplantation. Results: From Feb 2007 to Aug 2017, 28 patients with a small renal mass chose radical nephrectomy and were considered suitable for kidney donation after tumor excision. The tumor size was from 1 cm to 4 cm, average 2.7 cm. There were 24 malignant tumors; with most of them were Fuhrman grade I-II; and 4 benign tumors. The recipients age were from 52-80 years old; average 63 year old at the time for kidney transplantation M:F=15:13. The average warm ischemic time was 5 minutes; cold ischemic time was from 155 minutes to 340 minutes (average 275). In our cohort the follow up period was from 2-10 years, median 7 years. There was no tumor recurrence. Of recipients, 68% are alive with average age 70 years old at follow up. The average Cr level was136 mmol/L. At early phase 3 patients developed urine leakage from the tumor excision area and one patient developed pseudoaneurysm, but all recoved well after interventional management. Conclusion: Transplantation of tumourectomized kidneys from patients with small renal cell cancer is associated with comparable allograft and patient outcomes. The decision of utilizing these kidneys for transplantation needs careful informed consent process, balancing the benefit of kidney transplantation and the small but potential risk of tumour recurrence. The absence of tumor recurrence in this cohort may be associated with cold perfusion, which inhibits tumor cell proliferation and clear excision of tumor on bench table.